Enhancing learning outcomes of Social Studies with Numbered Head Together: case at SMP Negeri 6 Yogyakarta - Hutami, Trapsila Siwi; Azizah, Primanisa Inayati (Universitas Negeri Yogyakarta, 2024)
Learning outcomes play a crucial role in the educational process as they serve as indicators of students' learning success, often expressed in the form of grades or scores. However, at SMP Negeri 6 Yogyakarta, the social studies learning outcomes, particularly in the knowledge aspect, have not reached their full potential and require enhancement. One approach to address this issue is by implementing the Numbered Head Together learning method. This research project aims to assess the impact of the Numbered Head Together Method on improving social studies learning outcomes, specifically in the knowledge domain, within class VII C at SMP Negeri 6 Yogyakarta during the 2022/2023 academic year. The study adopts a Classroom Action Research (PTK) design and involves 32 grade VII C students as research participants. The research process consists of two cycles, encompassing planning, implementation, observation, and reflection. Data collection methods include both tests and non-tests, with instruments such as written tests, performance appraisal sheets, and product appraisal sheets. Data validity is ensured through the triangulation method technique. Qualitative analysis techniques, including data reduction, data presentation, and conclusion/verification, were used to analyze the research data. The results demonstrate the positive impact of implementing the Numbered Head Together method on social studies learning outcomes in class VII C at SMP Negeri 6 Yogyakarta. Notably, there was a consistent increase in the percentage of students achieving social studies learning outcomes of KKTPâ‰¥80 throughout the cycles. Additionally, this research project contributed to enhancing students' skills in critical discussions and the creation of mind maps.